Impact of Liquidity Management on the Profitability of Development Bank in Nepal - Chhetri, Hem Bahadur Kunwar (Journal of Economics and Management, 2023)
This research investigates the impact of liquidity management on the profitability of three development banks in Nepal: SDBL, MNBBL, and GBBL. Data was collected from books and financial annual reports, covering Fiscal Years 69/70 to 78/79, resulting in 30 observations. The study employed correlation analysis and regression analysis to examine the relationship between liquidity management indicators, which are, in this case, Cash Reserve Ratio (CRR), Credit Deposit Ratio (CDR), Non-Performing Assets (NPA), Total Liabilities and Total Assets Ratio (TLTA), and Deposit to Total Assets Ratio (DTA) and profitability of development banks, i.e., Return on Equity (ROE). The findings indicate that liquidity management indicators have varying effects on profitability. The correlation analysis reveals strong positive correlations between CRR and ROE and moderate positive correlations between CDR, TLTA, and DTA with ROE. Additionally, NPA exhibits a significant negative correlation with ROE. The regression analysis further confirms the overall significance of the model, with CRR having a statistically significant positive impact on ROE. Based on these findings, the study recommends that development banks focus on optimizing liquidity management by maintaining an appropriate CRR level. Strengthening credit risk management practices and reducing non-performing assets are also suggested to enhance profitability. These findings contribute to understanding liquidity management's impact on profitability in the context of development banks in Nepal and provide valuable insights for bank management and policymakers.